Weton Calculation in Marriage Among the Samin Tribe in Blora Regency: The Perspective of Custom and Myth - Agung Prasetyo Utomo; Muhammad Chairul Huda; Suraining Rosodor (Santara: Journal of Islamic Law and Humanity, 2026)
The integration of local traditions into Islamic marriage law presents a complex dynamic in Indonesia, particularly within the Samin community in Blora Regency, which firmly adheres to the tradition of weton calculation or “ilmu titen”. This study aims to analyze the legal standing of the weton tradition within the framework of Islamic law (‘urf) and to deconstruct its cultural meaning using Roland Barthes’ Semiotic Myth theory. Employing empirical legal research methods with a juridical-sociological approach, this qualitative study collected data through in-depth interviews, participatory observation, and documentation in Kediren Village, the historical center of Samin teachings. The results indicate that the weton tradition is systematically integrated into the Nyumuk, Nyuwito, and Paseksen marriage stages, where this calculation serves not as a fatalistic prediction, but as an instrument for psychological risk management and a form of cautious effort (ikhtiar). The study concludes that weton qualifies as ‘urf shahih (valid custom) as it has harmonized with the pillars of Islamic marriage without violating the principles of monotheistic faith (tauhid). Furthermore, as a semiotic myth, weton functions to naturalize cultural values into perceived natural truths, effectively maintaining the communal identity and social order of the Samin community amidst modernization